Comparison of Eye Movement Desensitization Reprocessing and Cognitive Behavioral Therapy as Adjunctive Treatments for Recurrent Depression: The European Depression EMDR Network (EDEN) Randomized Controlled Trial - Ostacoli, Luca; Carletto, Sara; Cavallo, Marco; Baldomir-Gago, Paula; Di Lorenzo, Giorgio; Fernandez, Isabel; Hase, Michael; Justo-Alonso, Ania; Lehnung, Maria; Migliaretti, Giuseppe; Oliva, Francesco; Pagani, Marco; et al. (Frontiers in Psychology, 2018)
Background: Treatment of recurrent depressive disorders is currently only moderately successful. Increasing evidence suggests a significant relationship between adverse childhood experiences and recurrent depressive disorders, suggesting that trauma-based interventions could be useful for these patients. Objectives: To investigate the efficacy of Eye Movement Desensitization and Reprocessing therapy (EMDR) in addition to antidepressant medication (ADM) in treating recurrent depression. Design: A non-inferiority, single-blind, randomized clinical controlled trial comparing EMDR or CBT as adjunctive treatments to ADM. Randomization was carried out by a central computer system. Allocation was carried out by a study coordinator in each center. Setting: Two psychiatric services, one in Italy and one in Spain. Participants: Eighty-two patients were randomized with a 1:1 ratio to the EMDR group (n = 40) or CBT group (n = 42). Sixty-six patients, 31 in the EMDR group and 35 in the CBT group, were included in the completers analysis. Intervention: 15 ± 3 individual sessions of EMDR or CBT, both in addition to ADM. Participants were followed up at 6-months. Main outcome measure: Rate of depressive symptoms remission in both groups, as measured by a BDI-II score <13. Results: Sixty-six patients were analyzed as completers (31 EMDR vs. 35 CBT). No significant difference between the two groups was found either at the end of the interventions (71% EMDR vs. 48.7% CBT) or at the 6-month follow-up (54.8% EMDR vs. 42.9% CBT). A RM-ANOVA on BDI-II scores showed similar reductions over time in both groups [F(6,59) = 22.501, p < 0.001] and a significant interaction effect between time and group [F(6,59) = 3.357, p = 0.006], with lower BDI-II scores in the EMDR group at T1 [mean difference = –7.309 (95% CI [–12.811, –1.806]), p = 0.010]. The RM-ANOVA on secondary outcome measures showed similar improvement over time in both groups [F(14,51) = 8.202, p < 0.001], with no significant differences between groups [F(614,51) = 0.642, p = 0.817]. Conclusion: Although these results can be considered preliminary only, this study suggests that EMDR could be a viable and effective treatment for reducing depressive symptoms and improving the quality of life of patients with recurrent depression. Trial registration: ISRCTN09958202.